The Effect of Biological Assets and Profitability on Company Value in Agricultural Companies on the Indonesia Stock Exchange in 2020-2024 - Wiliam, Albert; Amna, Luke Suciaty (LPPPIPublishing, 2026)
This study aims to analyze the influence of biological assets and profitability on firm value in agricultural companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study used a quantitative approach with multiple linear regression. The research sample was obtained through purposive sampling based on certain criteria, resulting in 15 agricultural companies with a total of 75 initial observations. After conducting a casewise diagnostic test, 15 outliers were removed, resulting in 60 observations for analysis. The data used were secondary data obtained from the companies' annual financial reports. The results of the classical assumption test indicated that the data met all assumptions, making it suitable for further analysis. The results of the study indicate that biological assets have a positive and significant effect on firm value, indicating that sound management and disclosure of biological assets can improve investor perceptions. Furthermore, profitability was also shown to have a positive and significant effect on firm value, indicating that a company's ability to generate profits is a crucial factor in increasing market confidence. Therefore, biological assets and profitability are determinants in increasing the value of agricultural companies in Indonesia.